Peran Keterlibatan Ayah dalam Pengasuhan dengan Konsep Diri Remaja Tunadaksa (Jurnal Psikologi Integratif, 2023)
One of the problems that often faced by the teenagers with physical disabilities is the negative self-concept. Self-concept is a description of a person affected by the environment. The negative self-concept could lead the teenagers into a higher level of juvenile delinquency. Father, as one of the family members has an important role in shaping self-concept on teenagers. Teenagers with adequate attention of a father would tend to feel loved and worth that could lead them to shape a positive self-concept.  The purpose of this quantitative-correlational was to determine the role of father involvement in self-concept of teenagers with physical disabilities.  The respondents of this research were teenagers with physical disabilities aged 13 – 19 years old with father in total 53 respondents. Sampling technique used in this research was non-probability by using purposive sampling. The instrument used was Father Involvement Scale (rxx’=0,904) and Self-Concept Scale (rxx’=0,930). Data analysis technique was simple linier regression analysis.  The result of study showed that there was significant correlation between father involvement in self-concept of teenagers with physical disabilities (R=0,452, p
Keywords: Keterlibatan Ayah; Konsep Diri; Pengasuhan; Remaja; Tunadaksa; Father Involvement; Parenting; Teenagers; Self Concept' physical disabilities